An acrylic resin and its preparation method
Patent Information
- Application Number
- CN202611290187.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-27
AI Technical Summary
在耐酸性方面,晶圆切割及化学蚀刻减薄工序中常涉及含氢氟酸等强酸性蚀刻液的处理,若胶层的耐酸性不足,酸液将渗透胶层到达被粘物表面,引发渗液、腐蚀或胶层溶胀剥离,导致芯片污染或崩边缺陷
本发明制得的丙烯酸树脂具有分子量分布窄、初始剥离强度高、UV减粘效率优异以及耐热性和耐酸性俱佳的综合性优势,能够充分满足半导体封装及精密电子加工领域对高性能UV减粘材料的应用需求,具有良好的工业应用前景和推广价值。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, specifically to an acrylic resin and its preparation method. Background Technology
[0002] Acrylic resins are widely used in pressure-sensitive adhesives, coatings, and inks due to their excellent water resistance, weather resistance, adhesive properties, and structural designability. In recent years, with the rapid development of industries such as semiconductor wafer manufacturing, chip packaging, and precision electronic device processing, the demand for UV-induced tack reduction pressure-sensitive adhesive materials has been increasing. UV-resistant tapes, as important process materials in integrated circuit packaging, not only need to provide sufficient stable adhesion before UV irradiation to fix the wafer and prevent displacement, but also need to achieve rapid release of adhesive adhesion after processing via UV irradiation to facilitate die pickup. Simultaneously, they must meet stringent heat and acid resistance requirements during processing.
[0003] Existing UV-cured acrylic resin technologies still have shortcomings in the following aspects: On the one hand, in order to achieve the UV-curing function, existing technologies usually need to introduce polymerizable double bonds into the side chains of acrylate copolymers (for example, by grafting hydroxyl groups through the reaction of ethyl isocyanate methacrylate MOI). However, the degree of grafting reaction and the uniformity of double bond distribution are difficult to control precisely, resulting in uneven crosslinking network after UV curing, which affects the viscosity reduction effect and peel stability.
[0004] On the other hand, the existing polymerization process of UV-resistant acrylic resins is difficult to effectively control the growth rate of molecular chains and the progress of double bond grafting reaction during polymerization, resulting in a wide molecular weight distribution of the product (PDI is usually greater than 1.6), which in turn affects the peel strength change rate and the consistency of the tack reduction effect during the UV tack reduction process.
[0005] Furthermore, for demanding processing scenarios such as semiconductor wafer dicing and chemical etching for thinning, the heat resistance and acid resistance of UV anti-adhesion films are key factors affecting chip yield. In processes such as wafer back-side grinding, chemical etching, or high-temperature baking, anti-adhesion films often need to withstand processing temperatures above 150°C. However, conventional acrylic pressure-sensitive adhesives have relatively low glass transition temperatures (Tg). At high temperatures, the mobility of molecular chain segments increases, significantly reducing the cohesive strength of the adhesive layer and making defects such as edge lifting, melt seepage, or residual adhesive after UV irradiation prone to occur. Regarding acid resistance, wafer dicing and chemical etching for thinning often involve treatment with strong acidic etching solutions such as hydrofluoric acid. If the acid resistance of the adhesive layer is insufficient, the acid will penetrate the adhesive layer to the surface of the adhered object, causing seepage, corrosion, or adhesive layer swelling and peeling, leading to chip contamination or edge chipping defects. Inhomogeneity of the cross-linked network can also cause acid to preferentially penetrate along local defect areas, further degrading acid resistance.
[0006] Therefore, developing an acrylic resin with a narrow molecular weight distribution, high initial adhesion and efficient UV anti-adhesion properties, as well as excellent heat resistance and acid resistance, and its preparation method, has important industrial application value for meeting the demand for high-performance UV anti-adhesion materials in the semiconductor packaging and precision electronic processing fields.
[0007] The above background information is provided only to aid in understanding the concept and technical solution of this application. It does not necessarily belong to the prior art of this application, nor does it necessarily provide technical guidance. In the absence of clear evidence that the above information was disclosed before the filing date of this application, the above background information should not be used to evaluate the novelty and inventiveness of this application. Summary of the Invention
[0008] The purpose of this invention is to provide an acrylic resin with a narrow molecular weight distribution, high initial adhesion and efficient UV tack reduction properties, as well as excellent heat resistance and acid resistance, and its preparation method.
[0009] To achieve the above objectives, the technical solution adopted by the present invention is as follows: This invention provides a method for preparing acrylic resin, which includes the following steps: (1) The first part of the solvent is put into the reactor and heated to the reflux temperature. The first monomer and the first part of the initiator are added to the reactor to carry out the polymerization reaction to obtain the prepolymer. The first monomer includes short-chain alkyl acrylate, medium-chain alkyl acrylate and long-chain alkyl acrylate, wherein the short-chain alkyl acrylate is selected from one or more acrylates with 1 to 4 alkyl carbon atoms, the medium-chain alkyl acrylate is selected from one or more acrylates with 7 to 9 alkyl carbon atoms, and the long-chain alkyl acrylate is selected from one or more acrylates with 18 to 22 alkyl carbon atoms. The initiator is a mixture of azo initiators and peroxide initiators; (2) Mix the second monomer, the first part of the third monomer and the second part of the solvent, and add the resulting mixture and dodecyl mercaptan to the reaction system of step (1); The second monomer is 3,4-epoxycyclohexyl methacrylate; The third monomer includes olefinic unsaturated carboxylic acids, hydroxyalkyl acrylates, trifunctional (meth)acrylates, and acrylamide; (3) Add the second part of the initiator, the second part of the third monomer and the third part of the solvent to the reaction system obtained in step (2). After reacting for a period of time, add the remaining initiator, the remaining third monomer and the fourth part of the solvent and continue the reaction. (4) Add the first part of the polymerization inhibitor and catalyst to the reaction system obtained in step (3), then add the curing agent, and detect the content of isocyanate groups (NCO) in the system until the content of isocyanate groups drops to a preset value (no special restrictions, can be set according to actual needs, preferably 0.1% or less); The curing agent is a compound mixture of isocyanate methacrylate and isophorone diisocyanate.
[0010] This invention employs a stepwise free radical solution polymerization process. Specifically, in the early stage of polymerization, all of the first monomer with a low glass transition temperature (Tg) is added to the reaction system at once, initially forming a flexible prepolymer (i.e., soft segment). This soft segment imparts good wettability and initial adhesion to the adhesive layer. Subsequently, in the middle stage of polymerization, a second monomer containing epoxy groups and a third monomer containing carboxyl, hydroxyl, amide groups, and multifunctional structures are added. These monomers grow on the already formed flexible prepolymer chain, forming a segmented structure of soft and hard segments (i.e., a segmented structure with alternating soft and hard segments) on the molecular chain. The amide groups contained in acrylamide can form an intramolecular hydrogen bond network with epoxy groups and hydroxyl groups, which helps to improve crosslinking density and acid resistance.
[0011] Simultaneously, in the addition stages of the second and third monomers, a trace amount of dodecyl mercaptan is added dropwise as a chain transfer agent. Through a moderate chain transfer reaction, excessive molecular chain growth is inhibited, resulting in a significant narrowing of the molecular weight distribution. The introduction of this trace mercaptan does not disrupt the orderly arrangement of the soft and hard segments, but rather ensures that each molecular chain has a relatively uniform chain length, achieving synergistic optimization of the narrow molecular weight distribution and the alternating soft and hard segment structure.
[0012] Furthermore, this invention employs a composite system of azo and peroxide initiators, and adds initiators in batches at different stages of the polymerization reaction, achieving stable maintenance of free radical concentration throughout the polymerization process and resulting in more uniform product molecular chain lengths. Combined with the synergistic regulation of trace amounts of thiols, this provides a crucial guarantee for narrowing the molecular weight distribution.
[0013] Thanks to this, the acrylic resin obtained by this invention has sufficient peel strength before UV irradiation to reliably fix the backing material (wafer, substrate, glass, etc.), and achieves rapid release of adhesion after UV irradiation due to the formation of a regular cross-linked network. Simultaneously, the orderly distribution of hard segments and the uniform and dense cross-linked network enable the resin to maintain structural integrity even at a high temperature of 160°C, and effectively block the penetration of strong acidic etching solutions such as hydrofluoric acid, fully meeting the stringent requirements of semiconductor packaging and precision electronic processing for the heat resistance and acid resistance of anti-adhesion films.
[0014] In some embodiments, the long-chain alkyl acrylate is an eicosyl acrylate.
[0015] In some embodiments, the medium-chain alkyl acrylate is isooctyl acrylate.
[0016] In some embodiments, the short-chain alkyl acrylate is methyl acrylate or butyl acrylate.
[0017] In some embodiments, the mass ratio of the short-chain alkyl acrylate, the medium-chain alkyl acrylate, and the long-chain alkyl acrylate is (5~8):(6~8):1, preferably (6~6.5):(6.8~7.2):1.
[0018] In some embodiments, the olefinic unsaturated carboxylic acid is acrylic acid.
[0019] In some embodiments, the hydroxyalkyl acrylate is hydroxyethyl acrylate.
[0020] In some embodiments, the trifunctional (meth)acrylate is trimethylolpropane trimethacrylate.
[0021] In some embodiments, the third monomer of the first portion is a mixture of olefinic unsaturated carboxylic acid, hydroxyalkyl acrylate, trifunctional (meth)acrylate and acrylamide, and the third monomer of the first portion accounts for 99% to 99.9% of the total mass of the third monomer.
[0022] In some embodiments, the second portion of the third monomer and the remaining third monomer are both hydroxyalkyl acrylates, and the second portion of the third monomer accounts for 0.05% to 0.5% of the total mass of the third monomer, such as 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.4%, and 0.5%.
[0023] In some embodiments, the mass ratio of the olefinic unsaturated carboxylic acid, hydroxyalkyl acrylate, trifunctional (meth)acrylate and acrylamide is (0.01~0.1):(6.5~8.5):1:(2.5~3).
[0024] In some embodiments, the mass ratio of the first monomer, the second monomer, and the third monomer is 1:(0.01~0.1):(0.4~0.7).
[0025] In some embodiments, the azo initiator is azobisisobutyronitrile (AIBN).
[0026] In some embodiments, the peroxide initiator is benzoyl peroxide.
[0027] In some embodiments, the mass ratio of the azo initiator to the peroxide initiator in the initiator is 1:(1.5~2.0).
[0028] In some embodiments, the first portion of the initiator accounts for 40% to 50% of the total mass of the initiator.
[0029] In some embodiments, the second part of the initiator accounts for 20% to 30% of the total weight of the initiator.
[0030] In some embodiments, the third portion of solvent and the fourth portion of solvent each independently account for 0.5% to 3% of the total solvent mass.
[0031] In some embodiments, the solvent further includes a fifth portion of solvent, which is used to dilute the catalyst and accounts for 20% to 40% of the total solvent mass.
[0032] In some embodiments, the preparation method further includes adding residual solvent to the reaction system obtained in step (4), wherein the residual solvent accounts for 5% to 15% of the total mass of the solvent.
[0033] In some embodiments, the polymerization inhibitor is butylated hydroxytoluene.
[0034] In some embodiments, the catalyst is an organobismuth. The organobismuth includes, but is not limited to, one or more of bismuth neodecanoate, bismuth laurate, and bismuth isooctanoate.
[0035] In some specific embodiments, the catalyst is mixed with the fifth solvent to form a mixture with a mass concentration of 0.01% to 0.5% before being added to the reaction system.
[0036] In some embodiments, the mass ratio of isocyanate methacrylate to isophorone diisocyanate in the curing agent is (5~10):1.
[0037] In some embodiments, the solvent is ethyl acetate.
[0038] In some embodiments, the first portion of solvent accounts for 30% to 45% of the total solvent mass.
[0039] In some embodiments, the second portion of solvent accounts for 15% to 25% of the total solvent mass.
[0040] In some embodiments, the third portion of solvent and the fourth portion of solvent each independently account for 0.5% to 3% of the total solvent mass.
[0041] In some embodiments, the preparation method further includes adding the remaining polymerization inhibitor and the remaining solvent to the reaction system obtained in step (4) to adjust the viscosity of the system to a preset range (no particular limitation, which can be designed according to actual needs).
[0042] In some embodiments, the raw materials for preparing the acrylic resin include: 550-700 parts by weight of solvent, 150-250 parts by weight of first monomer, 3-8 parts by weight of second monomer, 80-130 parts by weight of third monomer, 50-65 parts by weight of curing agent, 0.2-0.8 parts by weight of dodecyl mercaptan, 0.5-1 parts by weight of initiator, 0.1-0.5 parts by weight of catalyst, and 0.05-0.3 parts by weight of polymerization inhibitor.
[0043] In some specific embodiments, the raw materials for preparing the acrylic resin include: 550-700 parts by weight of solvent, 80-95 parts by weight of butyl acrylate, 95-105 parts by weight of isooctyl acrylate, 10-20 parts by weight of eicosyl acrylate, 0.1-1 parts by weight of methyl acrylate, 3-8 parts by weight of 3,4-epoxycyclohexyl methacrylate, 0.1-1 parts by weight of acrylic acid, 60-75 parts by weight of hydroxyethyl acrylate, 5-15 parts by weight of trimethylolpropane trimethacrylate, 20-30 parts by weight of acrylamide, 45-55 parts by weight of isocyanate methacrylate, 3-10 parts by weight of isophorone diisocyanate, 0.2-0.8 parts by weight of dodecyl mercaptan, 0.2-0.4 parts by weight of azobisisobutyronitrile, 0.4-0.6 parts by weight of benzoyl peroxide, 0.1-0.5 parts by weight of organobismuth and 0.05-0.3 parts by weight of butylated hydroxytoluene.
[0044] In some embodiments, the reaction system temperature in steps (2) and (3) is 70°C to 85°C.
[0045] In some embodiments, the reaction system temperature in step (4) is 50°C to 65°C.
[0046] In some embodiments, in step (3), the second part of the initiator, the second part of the third monomer and the third part of the solvent are added, and the reaction is carried out for 1.5h to 2h; then the remaining initiator, the remaining third monomer and the fourth part of the solvent are added, and the reaction is continued for 2h to 2.5h.
[0047] In another aspect, the present invention provides an acrylic resin prepared by the preparation method described above.
[0048] In some embodiments, the acrylic resin is a UV-resistant, tack-reducing acrylic resin.
[0049] Due to the application of the above-mentioned technical solution, the present invention has the following advantages compared with the prior art: The acrylic resin prepared by this invention has comprehensive advantages such as narrow molecular weight distribution, high initial peel strength, excellent UV de-tack efficiency, and good heat resistance and acid resistance. It can fully meet the application needs of high-performance UV de-tack materials in the fields of semiconductor packaging and precision electronic processing, and has good industrial application prospects and promotion value. Detailed Implementation
[0050] The present invention will be further described below with reference to embodiments. However, the present invention is not limited to the following embodiments. The implementation conditions used in the embodiments can be further adjusted according to different requirements of specific applications, and the implementation conditions not specified are conventional conditions in the industry. The technical features involved in the various embodiments of the present invention can be combined with each other as long as they do not conflict with each other.
[0051] In the following embodiments and comparative examples of the present invention, unless otherwise expressly stated, the reagents used are all commercially available products or can be prepared with reference to existing technology.
[0052] Example 1: This embodiment provides an acrylic resin, the raw material components of which are as follows: Solvent: 629.74 parts by weight of ethyl acetate; First monomer: 88.60 parts by weight of butyl acrylate, 98.30 parts by weight of isooctyl acrylate, 14.10 parts by weight of eicosyl acrylate and 0.32 parts by weight of methyl acrylate; Second monomer: 4.72 parts by weight of 3,4-epoxycyclohexyl methacrylate; The third monomer consists of 0.30 parts by weight of acrylic acid, 68.71 parts by weight of hydroxyethyl acrylate (of which 68.50 parts by weight are added with the third monomer mixture in step S2, and the remaining 0.21 parts by weight are added in steps S3 and S4 respectively with 0.105 parts by weight each), 9.15 parts by weight of trimethylolpropane trimethacrylate (TMPTMA), and 26.50 parts by weight of acrylamide; Curing agent: 51.60 parts by weight of ethyl isocyanate methacrylate (MOI) and 6.60 parts by weight of isophorone diisocyanate (IPDI); Molecular weight regulating agent: 0.42 parts by weight of dodecyl mercaptan; Initiator: 0.30 parts by weight of azobisisobutyronitrile (AIBN) and 0.48 parts by weight of benzoyl peroxide (BPO); Catalyst: 0.22 parts by mass of bismuth neodecanoate; Polymerization inhibitor: 0.15 parts by weight of butylated hydroxytoluene (BHT).
[0053] This embodiment also provides a method for preparing acrylic resin, which includes the following steps: S1. Add 235.20 parts by mass of ethyl acetate to the reactor and heat to 76℃~78℃ while maintaining reflux. After the reflux stabilizes, add the first monomer mixture (i.e., a mixture of 88.60 parts by mass of butyl acrylate, 98.30 parts by mass of isooctyl acrylate, 14.10 parts by mass of eicosyl acrylate, and 0.32 parts by mass of methyl acrylate) and 0.36 parts by mass of initiator (i.e., 0.14 parts by mass of AIBN and 0.22 parts by mass of BPO) separately and uniformly to the reactor over a period of 2.5 hours. After the addition is complete, maintain the temperature at 76℃~78℃ for 1 hour to obtain the prepolymer.
[0054] S2. Mix the second monomer (4.72 parts by mass of 3,4-epoxycyclohexyl methacrylate), the third monomer (0.30 parts by mass of acrylic acid, 68.50 parts by mass of hydroxyethyl acrylate, 9.15 parts by mass of TMPTMA and 26.50 parts by mass of acrylamide), and 123.20 parts by mass of ethyl acetate evenly. Then, add the mixture of the second and third monomers and dodecyl mercaptan to the reaction system of step S1 separately and at a uniform rate for 2.5-3 hours.
[0055] S3. Add 0.21 parts by mass of initiator (i.e., 0.08 parts by mass of AIBN and 0.13 parts by mass of BPO), 0.105 parts by mass of hydroxyethyl acrylate and 9.6 parts by mass of ethyl acetate to the reaction system obtained in step S2, and keep it at a constant temperature of 76℃~78℃ for 1.8h.
[0056] S4. Add 0.21 parts by mass of initiator (i.e., 0.08 parts by mass of AIBN and 0.13 parts by mass of BPO), 0.105 parts by mass of hydroxyethyl acrylate and 9.6 parts by mass of ethyl acetate to the reaction system obtained in step S3, and keep it at a constant temperature of 76℃~78℃ for 2.2h.
[0057] S5. Cool the reaction system obtained in step S4 to 55℃~58℃. Add 0.075 parts by mass of BHT (based on the total mass of BHT) and bismuth neodecanoate catalyst diluted with ethyl acetate (composed of 0.22 parts by mass of bismuth neodecanoate and 203.354 parts by mass of ethyl acetate) to the reactor and stir until homogeneous. Then, slowly add a mixture of IPDI and MOI dropwise. During the dropwise addition, the NCO content in the system is monitored in real time using online infrared spectroscopy. The reaction is considered complete when the NCO content drops below 0.1% (or is undetectable).
[0058] S6. Add the remaining BHT and ethyl acetate to the reaction system obtained in step S5, adjust the viscosity of the system to 2000 mPa·s~3000 mPa·s (25℃, test method refers to GB / T 2794-2022 "Determination of viscosity of adhesives"), continue stirring until homogeneous, and discharge the material.
[0059] The polymerization reaction in this embodiment has good controllability, small batch-to-batch molecular weight fluctuation, and excellent process reproducibility.
[0060] The structure of the obtained product was characterized using infrared spectroscopy, and the main characteristic peaks in its infrared absorption spectrum and their assignments are as follows: At 1720 cm -1 The strong absorption peak at this point is attributed to the stretching vibration of the carbonyl group (C=O) in the acrylate copolymer; At 1650 cm -1 An absorption peak appears at this point, which is attributed to the amide I band (C=O stretching vibration) in the acrylamide structural unit. At 910 cm -1 The absorption peak at this point is attributed to the symmetric stretching vibration of the epoxy group (COC) in the 3,4-epoxycyclohexyl methacrylate structural unit, indicating that the epoxy group is retained during the polymerization process. At 810 cm -1 The absorption peak appears at this point, which is attributed to the residual terminal carbon-carbon double bond (=CH2 out-of-plane bending vibration) in the TMPTMA structural unit, providing crosslinking sites for subsequent UV curing; At 3300~3500 cm -1 The presence of broad and strong absorption peaks within the range is attributed to the stretching vibrations of hydroxyl (-OH) or amino (NH) groups, indicating the presence of strong hydrogen bonding association within the system.
[0061] Comparative Example 1: This comparative example provides an acrylic resin and its preparation method, which is basically the same as that in Example 1, except that dodecyl acrylate is used instead of eicosyl acrylate in equal mass. That is, the first monomer component is: 88.60 parts by mass of butyl acrylate, 98.30 parts by mass of isooctyl acrylate, 14.10 parts by mass of dodecyl acrylate and 0.32 parts by mass of methyl acrylate.
[0062] Comparative Example 2: This comparative example provides an acrylic resin and its preparation method, which are basically the same as those in Example 1, except that the raw material formulation does not contain 3,4-epoxycyclohexyl methacrylate.
[0063] Specifically, in step S2, the components of the third monomer (0.30 parts by mass of acrylic acid, 68.50 parts by mass of hydroxyethyl acrylate, 9.15 parts by mass of TMPTMA, and 26.50 parts by mass of acrylamide) are mixed evenly. Then, the third monomer mixture and dodecyl mercaptan are added to the reaction system of step S1 separately and at a uniform rate over a period of 2.5 to 3 hours. The remaining steps and parameters are the same as in Example 1.
[0064] Comparative Example 3: This comparative example provides an acrylic resin and its preparation method, which is basically the same as that in Example 1, except that the raw material formulation does not contain TMPTMA.
[0065] Specifically, in step S2, the second monomer (4.72 parts by mass of 3,4-epoxycyclohexyl methacrylate) is mixed thoroughly with the remaining components of the third monomer (excluding TMPTMA) (0.30 parts by mass of acrylic acid, 68.50 parts by mass of hydroxyethyl acrylate, and 26.50 parts by mass of acrylamide). Then, this mixture and dodecyl mercaptan are added separately and at a uniform rate to the reaction system of step S1 over a period of 2.5–3 hours. The remaining steps and parameters are the same as in Example 1.
[0066] Comparative Example 4: This comparative example provides an acrylic resin and its preparation method, which is basically the same as that in Example 1, except that the raw material formulation does not contain IPDI, and MOI with an equi-NCO molar equivalent is used to replace IPDI.
[0067] Specifically, the curing agent composition is: 60.82 parts by weight of MOI, excluding IPDI. The remaining steps and parameters are the same as in Example 1.
[0068] Comparative Example 5: This comparative example provides an acrylic resin and its preparation method, which is basically the same as that in Example 1, except that the raw material formulation does not contain dodecyl mercaptan.
[0069] Specifically, in step S2, the second monomer (4.72 parts by mass of 3,4-epoxycyclohexyl methacrylate) and the third monomer (0.30 parts by mass of acrylic acid, 68.50 parts by mass of hydroxyethyl acrylate, 9.15 parts by mass of TMPTMA, and 26.50 parts by mass of acrylamide) are mixed evenly, and then the mixture is added directly to the reaction system of step S1 at a uniform rate, while dodecyl mercaptan is added dropwise without synchronization. The remaining steps and parameters are the same as in Example 1.
[0070] Comparative Example 6: This comparative example provides an acrylic resin and its preparation method, which is basically the same as that in Example 1, except that the order of adding materials in the preparation method is different, that is, the timing of adding the second monomer and the third monomer in steps is different from that in Example 1.
[0071] The specific steps are as follows: Step S1: Add 235.20 parts by mass of ethyl acetate to the reactor, heat to 76℃~78℃ and maintain reflux. After the reflux stabilizes, add the first monomer mixture (88.60 parts by mass of butyl acrylate, 98.30 parts by mass of isooctyl acrylate, 14.10 parts by mass of eicosyl acrylate and 0.32 parts by mass of methyl acrylate), the second monomer (4.72 parts by mass of 3,4-epoxycyclohexyl methacrylate), and part of the initiator (0.14 parts by mass of AIBN and 0.22 parts by mass of BPO) to the reactor separately and at a uniform rate for 2.5 hours. After the addition is complete, maintain the temperature at 76℃~78℃ for 1 hour to obtain the prepolymer.
[0072] Step S2: Mix the third monomer (0.30 parts by mass of acrylic acid, 68.50 parts by mass of hydroxyethyl acrylate, 9.15 parts by mass of TMPTMA and 26.50 parts by mass of acrylamide) with 123.20 parts by mass of ethyl acetate. Then add the third monomer mixture and dodecyl mercaptan to the reaction system of step S1 separately at a uniform rate for 2.5-3 hours.
[0073] The remaining steps S3 to S6 are the same as in Example 1.
[0074] Due to the change in the feeding sequence, the controllability of the polymerization process changed, resulting in some fluctuations in the batch performance of this comparative example. To objectively reflect its performance, this comparative example underwent three parallel experiments, and the data listed in Table 1 are the numerical ranges of the results for each experiment.
[0075] Performance testing: 1. Weight-average molecular weight (Mw): The detection method refers to GB / T 36214.1-2018 "Determination of average molecular weight and molecular weight distribution of polymers by volume displacement chromatography".
[0076] 2. Polydispersity Index (PDI): The number-average molecular weight (Mn) and weight-average molecular weight (Mw) were determined by gel permeation chromatography (GPC), and calculated using the formula PDI = Mw / Mn. Specific procedures are detailed in GB / T 27810-2011 "Gel Permeation Chromatography (GPC) for Paints and Varnishes - Using Tetrahydrofuran as Eluent".
[0077] 3. Peel strength: The test method for peel strength of adhesive tape to stainless steel at 180° is specified in GB / T 2792-2014 "Test method for peel strength of adhesive tape".
[0078] 4. Heat resistance: The sample is made by attaching it to the surface of SUS steel plate using a 2kg standard roller. It is placed in a constant temperature oven at (160±2)℃ for 3 hours. After cooling to room temperature (25±2)℃, it is subjected to UV irradiation. After irradiation, the surface condition of the adhesive layer is observed: if there is no residual adhesive, no curling, and no adhesive seepage, the heat resistance is judged to be "qualified"; if there is residual adhesive, curling, or adhesive seepage, it is judged to be unqualified.
[0079] 5. Acid Resistance: The sample is made by attaching a 2kg standard roller to the surface of the SUS steel plate and immersing it in a 9% hydrofluoric acid aqueous solution for 30 minutes. After rinsing with deionized water and drying, the sample is adhered to the coating surface with 3M 600 tape (or equivalent), pressed flat with constant pressure, and then quickly peeled off. If there is no residue, peeling, whitening, or seepage in the coating, the acid resistance is deemed "qualified". If there is residue, peeling, whitening, or seepage, the sample is deemed unqualified.
[0080] The performance tests of the acrylic resins in the above embodiments and comparative examples are shown in Table 1 below.
[0081] Table 1 In Table 1: the peel force data of Comparative Example 4 is the fluctuation range caused by the instability of the test value when a single sample is repeatedly tested; Comparative Examples 5 and 6 were each conducted in 3 parallel experiments due to the poor controllability of the polymerization reaction and the obvious fluctuation of performance between batches. The data listed in the table are the numerical range of the results of each experiment.
[0082] As shown in Table 1, the acrylic resin obtained in Example 1 of the present invention has a suitable weight-average molecular weight (682,000) and a narrow molecular weight distribution (PDI=1.18), indicating that the technical solution of the present invention can obtain an acrylic resin with controllable molecular weight and uniform distribution.
[0083] In contrast, when dodecyl acrylate was used to replace eicosyl acrylate in Comparative Example 1, the PDI increased significantly to 1.62, and the heat resistance decreased (resin residue appeared). This indicates that the long-chain alkyl structure of eicosyl acrylate helps to stabilize the composition distribution and phase state of the polymerization system, and plays an important role in maintaining the uniformity of the resin's molecular weight distribution and heat resistance.
[0084] In Comparative Example 2, the PDI was slightly increased to 1.23 after the absence of 3,4-epoxycyclohexyl methacrylate, but it was still relatively narrow. However, the heat resistance showed edge curling and the acid resistance showed leakage, indicating that the introduction of epoxy groups is crucial to improving the heat resistance and acid resistance of the resin.
[0085] In Comparative Example 3, the PDI increased to 1.34 after the absence of TMPTMA, and the peel strength increased significantly (15.1 N / 25 mm before UV and 0.32 N / 25 mm after UV). However, residual adhesive and acid seepage were observed in the heat resistance, indicating that TMPTMA, as a multifunctional crosslinking monomer, has a synergistic effect on building a uniform crosslinking network and balancing peel strength with heat and acid resistance.
[0086] In Comparative Example 4, after replacing the diisocyanate IPDI with an equal molar equivalent of monoisocyanate MOI (-NCO), the PDI increased to 1.33, and the peel strength test showed unstable fluctuations (14~18N before UV, 0.3~0.5N after UV). It also showed heat resistance, residual adhesive resistance, and acid penetration resistance, indicating that the bifunctional structure of IPDI is indispensable for forming a stable crosslinking network and ensuring performance consistency and reliability.
[0087] In Comparative Example 5, the controllability of the polymerization reaction was significantly reduced (Mw fluctuated between 635,000 and 718,000, PDI = 1.75) due to the lack of the molecular weight regulating agent dodecyl mercaptan. Furthermore, all properties were significantly deteriorated, indicating that dodecyl mercaptan plays a crucial role in regulating molecular weight and its distribution, and ensuring batch stability of the product.
[0088] After changing the feeding sequence in Comparative Example 6 (adding the second monomer in the S1 stage), the controllability of polymerization also deteriorated (Mw fluctuated between 703,000 and 727,000, PDI = 1.68), and the heat resistance curled and the acid resistance leaked out. This shows that the technical feature of adding the second and third monomers together in the S2 stage is the key process condition for obtaining excellent comprehensive performance.
[0089] In summary, this invention, through a specific combination of monomers in specific types and amounts (especially the synergistic use of eicosyl acrylate, 3,4-epoxycyclohexyl methacrylate, and TMPTMA), suitable additives, and an optimized stepwise feeding process, has obtained a UV-controlled tack-reducing acrylic resin with controllable molecular weight, narrow molecular weight distribution, moderate peel strength, and excellent heat and acid resistance, which has good prospects for industrial application.
[0090] The present invention has been described in detail above, with the aim of enabling those skilled in the art to understand and implement the invention. However, this description should not be construed as limiting the scope of protection of the invention. All equivalent changes or modifications made in accordance with the spirit and essence of the invention should be included within the scope of protection of the invention.
Claims
1. A method for preparing an acrylic resin, characterized in that, Includes the following steps: (1) The first part of the solvent is put into the reactor and heated to the reflux temperature. The first monomer and the first part of the initiator are added to the reactor to carry out the polymerization reaction to obtain the prepolymer. The first monomer includes short-chain alkyl acrylate, medium-chain alkyl acrylate and long-chain alkyl acrylate, wherein the short-chain alkyl acrylate is selected from one or more acrylates with 1 to 4 alkyl carbon atoms, the medium-chain alkyl acrylate is selected from one or more acrylates with 7 to 9 alkyl carbon atoms, and the long-chain alkyl acrylate is selected from one or more acrylates with 18 to 22 alkyl carbon atoms. The initiator is a mixture of azo initiators and peroxide initiators; (2) Mix the second monomer, the first part of the third monomer and the second part of the solvent, and add the resulting mixture and dodecyl mercaptan to the reaction system of step (1); The second monomer is 3,4-epoxycyclohexyl methacrylate; The third monomer includes olefinic unsaturated carboxylic acids, hydroxyalkyl acrylates, trifunctional (meth)acrylates, and acrylamide; (3) Add the second part of the initiator, the second part of the third monomer and the third part of the solvent to the reaction system obtained in step (2). After reacting for a period of time, add the remaining initiator, the remaining third monomer and the fourth part of the solvent and continue the reaction. (4) Add the first part of the polymerization inhibitor and catalyst to the reaction system obtained in step (3), then add the curing agent, and detect the content of isocyanate groups in the system until the content of isocyanate groups drops below the preset value; The curing agent is a compound mixture of isocyanate methacrylate and isophorone diisocyanate.
2. The method for preparing acrylic resin according to claim 1, characterized in that, The long-chain alkyl acrylate is an eicosyl acrylate; And / or, the medium-chain alkyl acrylate is isooctyl acrylate; And / or, the short-chain alkyl acrylate is methyl acrylate and butyl acrylate; And / or, the mass ratio of the short-chain alkyl acrylate, medium-chain alkyl acrylate, and long-chain alkyl acrylate is (5~8):(6~8):
1.
3. The method for preparing acrylic resin according to claim 1, characterized in that, The olefinic unsaturated carboxylic acid is acrylic acid; And / or, the hydroxyalkyl acrylate is hydroxyethyl acrylate; And / or, the trifunctional (meth)acrylate is trimethylolpropane trimethacrylate; And / or, the third monomer in the first portion is a mixture of olefinic unsaturated carboxylic acids, hydroxyalkyl acrylates, trifunctional (meth)acrylates, and acrylamide, wherein the third monomer in the first portion accounts for 99% to 99.9% of the total mass of the third monomer; And / or, the second portion of the third monomer and the remaining third monomer are both hydroxyalkyl acrylates, and the second portion of the third monomer accounts for 0.05% to 0.5% of the total mass of the third monomer; And / or, the mass ratio of the olefinic unsaturated carboxylic acid, hydroxyalkyl acrylate, trifunctional (meth)acrylate and acrylamide is (0.01~0.1):(6.5~8.5):1:(2.5~3).
4. The method for preparing acrylic resin according to claim 1, characterized in that, The mass ratio of the first monomer, the second monomer, and the third monomer is 1:(0.01~0.1):(0.4~0.7).
5. The method for preparing acrylic resin according to claim 1, characterized in that, The azo initiator is azobisisobutyronitrile; And / or, the peroxide initiator is benzoyl peroxide; And / or, the mass ratio of azo initiator to peroxide initiator in the initiator is 1:(1.5~2.0); And / or, the first portion of the initiator accounts for 40% to 50% of the total mass of the initiator; And / or, the second part of the initiator accounts for 20% to 30% of the total weight of the initiator.
6. The method for preparing acrylic resin according to claim 1, characterized in that, The polymerization inhibitor is butylated hydroxytoluene; And / or, the catalyst is an organic bismuth; And / or, the mass ratio of isocyanate methacrylate to isophorone diisocyanate in the curing agent is (5~10):
1.
7. The method for preparing acrylic resin according to claim 1, characterized in that, The solvent is ethyl acetate; And / or, the first portion of solvent accounts for 30% to 45% of the total solvent mass; And / or, the second portion of solvent accounts for 15% to 25% of the total solvent mass; And / or, the third portion of solvent and the fourth portion of solvent each independently account for 0.5% to 3% of the total solvent mass; And / or, the solvent further includes a fifth portion of solvent, the fifth portion of solvent being used to dilute the catalyst, the fifth portion of solvent accounting for 20% to 40% of the total solvent mass; And / or, the preparation method further includes adding the remaining solvent to the reaction system obtained in step (4), wherein the remaining solvent accounts for 5% to 15% of the total mass of the solvent.
8. The method for preparing acrylic resin according to claim 1, characterized in that, The preparation method further includes adding the remaining polymerization inhibitor and the remaining solvent to the reaction system obtained in step (4) and adjusting the viscosity of the system to a preset range.
9. The method for preparing the acrylic resin according to any one of claims 1 to 8, characterized in that, The raw materials for preparing the acrylic resin include: 550-700 parts by weight of solvent, 150-250 parts by weight of first monomer, 3-8 parts by weight of second monomer, 80-130 parts by weight of third monomer, 50-65 parts by weight of curing agent, 0.2-0.8 parts by weight of dodecyl mercaptan, 0.5-1 parts by weight of initiator, 0.1-0.5 parts by weight of catalyst, and 0.05-0.3 parts by weight of polymerization inhibitor.
10. The method for preparing acrylic resin according to claim 1, characterized in that, The reaction system temperature in steps (2) and (3) is 70℃~85℃; And / or, the reaction system temperature in step (4) is 50℃~65℃.
11. The acrylic resin prepared by any one of claims 1 to 10.
12. The acrylic resin according to claim 11, characterized in that, The acrylic resin is a UV-resistant acrylic resin that can reduce tack.